The Global Financial Crisis: Management of Deficits and Debts - Constantin Ciutacu; Luminita Chivu; Raluca Iorgulescu (Amfiteatru Economic Journal, 2009)
The boom of world trade, the unprecedented openness of domestic markets, regional integration, and the persistence and magnitude of globalisation are as many challenges to the management of the internal balance between revenues and expenditures, both in the context of international, regional, national, and company mechanisms, and for the individual households and consumers. The coexistence of foreign deficits/trade and domestic deficits/ budget at macro level, at the same time with the accumulation of high levels of indebtedness of the states, non-financial corporate entities, and individual households requires, in the context of the present global financial crisis, new theoretical and practical approaches, new institutions, and new policies capable to secure the sustainability of growth, and to diminish the risk of increasingly unpredictable disturbances.
Keywords: F34; H63; H74; 330; global financial crisis; deficit management; indebtness rate; net landing and net borrowing; foreign/trade deficit; domestic/budgerary deficit